Real-World Treatment Outcomes in Black, Hispanic, Asian, and White People with Multiple Sclerosis Treated with Fumarates in the USA - Sophia Woodson; Edward J. Gettings; Chu-Yueh Guo; Sylvia Klineova; Jong-Mi Lee; Rebecca S. Romero; Aljoeson Walker; Kinyee Fong; Jason P. Mendoza; Nicholas Belviso; Boyang Bian; James B. Lewin; et al. (Neurology and Therapy)
Abstract Introduction Multiple sclerosis (MS) is a heterogeneous disease affecting a diverse population. Compared with white people with MS (PwMS), Black PwMS have more severe disease and higher incidence of MS, whereas Hispanic PwMS experience earlier onset disease; however, MS is not adequately studied in these groups. We compared the effectiveness of fumarates across Black, Hispanic, Asian, and white PwMS. Methods This retrospective analysis using the Komodo Health database included PwMS. Patients with a claim for diroximel fumarate or dimethyl fumarate were followed from disease-modifying therapy (DMT) initiation to loss of follow-up or discontinuation. Outcomes included annualized relapse rate (ARR), time to post-index first relapse, healthcare resource use (HRU), healthcare costs (HCCs), and change in absolute lymphocyte counts (ALCs). Race/ethnicity was self-reported. Results This study included 6800 PwMS (Black, n = 1241; Hispanic, n = 777; Asian, n = 132; white, n = 4650). The average exposure duration of fumarates was 449–559 days. Black PwMS had higher baseline disease burden versus white PwMS, were less likely to have commercial insurance plans, and were more likely to reside in a state with a higher poverty rate. ARRs (12-month pre-index to post-index) were significantly reduced across groups. The Kaplan–Meier estimated proportion of relapse-free patients at 2 years was similar across groups (Black, 77.0%; Hispanic, 75.4%; Asian, 81.7%; white, 80.5%). There was a smaller decline in ALC from month 0 to month 12 in Black PwMS versus other racial/ethnic groups. Conclusion Consistent with prior studies, these results demonstrate the effectiveness of fumarates across racial and ethnic MS subgroups. This is the largest analysis to date of the treatment effects of any individual class of DMT in Black and Hispanic PwMS. Infographic available for this article.